2017
DOI: 10.3389/fphar.2017.00543
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis Provides insight into the Key Proteins as Possible Targets Involved in Aspirin Inhibiting Biofilm Formation of Staphylococcus xylosus

Abstract: Staphylococcus xylosus is an opportunistic pathogen that causes infection in humans and cow mastitis. And S. xylosus possesses a strong ability to form biofilms in vitro. As biofilm formation facilitates resistance to antimicrobial agents, the discovery of new medicinal properties for classic drugs is highly desired. Aspirin, which is the most common active component of non-steroidal anti-inflammatory compounds, affects the biofilm-forming capacity of various bacterial species. We have found that aspirin effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 61 publications
(77 reference statements)
0
36
1
1
Order By: Relevance
“…In order to construct a metabolic network of identified lipids, we integrated interaction databases: Reactome, Database for Annotation, Visualization and Integrated Discovery (DAVID), Kyoto Encyclopedia of Genes and Genomes (KEGG), Biomolecular Interaction Network Database (BIND), Human Protein Reference Database (HPRD), BioGrid, Database of Interacting Proteins (DIP), Metabolite Set Enrichment Analysis (MSEA), and Quantitative Enrichment Analysis (QEA) (Xenarios et al, 2002 ; Bader et al, 2003 ; Huang da et al, 2009 ; Goel et al, 2012 ; Xu et al, 2017 ). These databases contained the most comprehensive publicly available repository of genes, proteins, and interaction of complexes for Homo sapiens.…”
Section: Methodsmentioning
confidence: 99%
“…In order to construct a metabolic network of identified lipids, we integrated interaction databases: Reactome, Database for Annotation, Visualization and Integrated Discovery (DAVID), Kyoto Encyclopedia of Genes and Genomes (KEGG), Biomolecular Interaction Network Database (BIND), Human Protein Reference Database (HPRD), BioGrid, Database of Interacting Proteins (DIP), Metabolite Set Enrichment Analysis (MSEA), and Quantitative Enrichment Analysis (QEA) (Xenarios et al, 2002 ; Bader et al, 2003 ; Huang da et al, 2009 ; Goel et al, 2012 ; Xu et al, 2017 ). These databases contained the most comprehensive publicly available repository of genes, proteins, and interaction of complexes for Homo sapiens.…”
Section: Methodsmentioning
confidence: 99%
“…It is pivotal to construct the 3D IGPD structure based on the known structures by homology modeling method. The amino acid sequences of the IGPD protein were isobarically tagged for relative and absolute quantitation (iTRAQ) labeling (Xu et al, 2017 ; Table 1 ). Hence, sequence similarity searches were carried out by utilizing BLASTp analysis (Altschul et al, 1990 ), which revealed suitable templates for the homology modeling.…”
Section: Methodsmentioning
confidence: 99%
“…S. xylosus is also one of the coagulase-negative staphylococci (CoNS) (Osman et al, 2016 ), which has strong ability of biofilm formation (Planchon et al, 2006 , 2009 ). In addition, the L-histidine synthesis pathway is involved in the formation of biofilm in S. xylosus (Xu et al, 2017 ). The imidazole glycerophosphate dehydratase (IGPD), one of the specific enzymes, catalyzes the dehydration of imidazoleglycerol phosphate (IGP) to imidazoleacetol phosphate (IAP) (Hawkes et al, 1995 ), which synthesize L-histidine in the synthesis pathway (Dietl et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other genes involved in amino-acid biosynthetic pathways were down-regulated, including (SE0275, -7-fold); this gene encodes 1-(5-phosphoribosyl)-5-[(5-phosphoribosylamino) methylideneamino] imidazole-4-carboxamide isomerase, which is involved in L-histidine biosynthesis. Down-regulation of hisA was also seen for Staphylococcus xylosus after exposure to aspirin [60]. Ketol-acid reductoisomerase (SE1657, -8.1-fold) is involved in branched-chain amino-acid biosynthesis [61].…”
Section: Response Mechanisms To Ddac Of the Ddac-tolerant S Epidermimentioning
confidence: 96%